Biochemical characterization of LR769, a new recombinant factor VIIa bypassing agent produced in the milk of transgenic rabbits. Issue 4 (8th June 2017) - Chevreux, G.; Tilly, N.; Leblanc, Y.; Ramon, C.; Faid, V.; Martin, M.; Dhainaut, F.; Bihoreau, N.
Abstract : Background: The bypassing agent factor VII (FVIIa) is a first‐line therapy for the treatment of acute bleeding episodes in patients with haemophilia and high‐titre inhibitors. FVIIa is a highly post‐translationally modified protein that requires eukaryotic expression systems to produce a fully active molecule. A recombinant FVIIa was produced in the milk of transgenic rabbits to increase expression and provide an efficient, safe and affordable product after purification to homogeneity (LR769). Aim: To present the biochemical and functional in vitro characteristics of LR769. Results: Mass spectrometric analyses of the intact protein and of heavy and light chains revealed a fully activated, mature and properly post‐translationally modified protein notably regarding N/O‐glycosylations and γ‐carboxylation. Primary structure analysis, performed by peptide mapping, confirmed 100% of the sequence and the low level or absence of product‐derived impurities such as oxidized, deamidated and glycated forms. Low levels of aggregates and fragments were observed by different chromatographic methods. Higher order structure investigated by circular dichroism showed appropriate secondary/tertiary structures and conformational change in the presence of Ca 2+ ions. Finally, activated partial thromboplastin time and thrombin generation assays showed the ability of LR769 to decrease coagulation time and to generate thrombin in haemophiliac‐A‐plasmas, even in the presence of inhibitors. Conclusion: The innovative expression system used to produce LR769 yields a new safe and effective rhFVIIa for the treatment of haemophilia A or B patients with inhibitors.